Managing a stigmatized identity—evidence from a longitudinal analysis about people with mental illness. Issue 7 (28th February 2014) - Ilic, Marie; Reinecke, Jost; Bohner, Gerd; Röttgers, Hans‐Onno; Beblo, Thomas; Driessen, Martin; Frommberger, Ulrich; Corrigan, Patrick William
Abstract Previous research about coping with the stigma of mental illness mostly relied on cross‐sectional or qualitative research designs. In the present study, the consequences of ten identity management strategies for mental illness stigma were observed in a longitudinal design. Cross‐lagged analyses were used to describe the influence of the strategies on the frequency of stigma experiences and on mental health in a two‐wave panel of people with mental illness (n = 367, 79% repeated response rate). Selective disclosure and information seeking emerged as adaptive identity management strategies, whereas overcompensation and withdrawal led to lower mental health. Results were mostly unaffected by demographic and psychiatric variables. The results support an empowerment model of stigma resilience that portrays stigmatized people as active constructors of their social world.